Aiming at reproducibility in lining canvas paintings - Antonio Iaccarino Idelson; Valerio Garofalo (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper describes a process started in 2011 with the use of the “mist lining” technique for a large painting by Titian, conserved in Venice uncontrolled environment. After several experiences with a specific version of the method, Valerio Garofalo’s research thesis helped the standardisation of lining procedures aiming to obtain predictable, reproducible results. This was achieved through the production of a large quantity of mock-up painting linings and samples for peel tests. The bond created with a viscoelastic adhesive appears stronger with high speed testing, if compared with the same at a lower speed, but literature shows high variability of peel speeds. Preliminary tests with different speeds for Plextol B500 allowed to compare results with literature data. The study gives a deeper understanding of the mechanisms involved in adhesion when lining with this method.